Circumstellar chemistry of Si-C bearing molecules in the C-rich AGB star IRC+10216. Issue Volume 14:Issue S343(2019) (August 2018) - Velilla-Prieto, L.; Cernicharo, J.; Agúndez, M.; Fonfría, J. P.; Castro-Carrizo, A.; Quintana-Lacaci, G.; Marcelino, N.; McCarthy, M. C.; Gottlieb, C. A.; Sánchez Contreras, C.; Young, K. H.; Patel, N. A.; et al.
Abstract: Silicon carbide together with amorphous carbon are the main components of dust grains in the atmospheres of C-rich AGB stars. Small gaseous Si-C bearing molecules (such as SiC, SiCSi, and SiC2 ) are efficiently formed close to the stellar photosphere. They likely condense onto dust seeds owing to their highly refractory nature at the lower temperatures (i.e., below about 2500 K) in the dust growth zone which extends a few stellar radii from the photosphere. Beyond this region, the abundances of Si-C bearing molecules are expected to decrease until they are eventually reformed in the outer shells of the circumstellar envelope, owing to the interaction between the gas and the interstellar UV radiation field. Our goal is to understand the time-dependent chemical evolution of Si-C bond carriers probed by molecular spectral line emission in the circumstellar envelope of IRC+10216 at millimeter wavelengths.